A content analysis of online videos containing dietary recommendations for gout and their alignment with evidence-based dietary guidelines - Kirstie Louise Lamb; Margo E Barker; Anthony Lynn (Cambridge University Press, 2023)
Abstract Objective: To assess the alignment of YouTube® videos providing dietary recommendations for gout with evidence-based guidelines targeted at the United Kingdom (UK) population and to establish their quality. Design: A content analysis of YouTube® videos providing dietary recommendations for gout was undertaken. Videos were categorised by video source. Each video's dietary recommendations for gout were compared with three evidence-based guidelines for gout, producing a compliance score. Presence of non-guideline advice was assessed. Understandability and actionability were evaluated using the Patient Education Material Assessment Tool for Audio-Visual Materials. Reliability was assessed using an adapted-DISCERN tool and educational quality using the Global Quality Score Five-Point Scale. Differences between video source and continuous variables were assessed using one-way Kruskal-Wallis H tests. For categorical variables, associations were investigated using Fisher-Freeman-Halton tests. Setting: Online, May-June 2020. Participants: One-hundred thirty-one videos. Results: Alignment of videos with evidence-based guidelines was poor (median compliance score 27 % (interquartile range 17-37 %)). Additionally, 57 % of videos contained non-guideline advice. The health professional source group had the fewest videos containing non-guideline advice, but this was only significantly lower than the naturopath group (31 % v. 81 %, P = 0·009). Almost 70 % of videos were considered poorly actionable and 50 % poorly understandable. Most videos were rated poor for reliability (79 %) and poor to generally poor for educational quality (49 %). Conclusions: YouTube® videos providing dietary recommendations for gout frequently fail to conform to evidence-based guidelines, and their educational quality, reliability, understandability and actionability are often poor. More high-quality, comprehensive, evidence-based YouTube® videos are required for UK gout patients.